(untitled) (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
The purpose of the study was to analyze the causes of the role of Protocol and Leadership Communications in improving the performance of the Magelang Regency Government that was still not optimal and to formulate efforts to improve the Role of Leaders’ Protocols and Communications in improving the performance of the Magelang Regency Government.The research method that will be used in this research is qualitative research. The subjects in this study were 1 Head of the Protocol and Communications Section of the Regional Secretariat of Magelang Regency, 1 Head of the Protocol Subdivision, and 1 Head of the Leadership Communications Subdivision. To process and analyze the data, the author uses an interactive data model as proposed by Miles and Huberman (1992). The results of this study indicate that the role of Protocol and Leadership Communication in improving the performance of the Magelang Regency Government, among others, is in facilitating Regional Leadership Communication, Reporting, Editorial and Publication activities and protocol facilitation starting from activity plans and protocol services for all forms of events carried out by the Magelang Regency government. Efforts to increase the role of Protocol and Leadership Communications in improving the performance of the Magelang Regency Government, namely Increasing teamwork or solid teamwork and high discipline because it is related to the speed of service to Regional Leaders, Increasing the ability to communicate, both internally (leaders and fellow employees) and externally (community). public or external parties) and improve employee competence, Increase cooperation between the Ministry of Communication and Informatics with the Protocol and Communications Division of the leadership as well as cooperation with several media belonging to the Regional Government to convey information to the public such as Radio Gemilang, Suara Gemilang Magazine, Magelang News online portal, WKM ( Forum for Community Communication), KIM (Community Information Group) and outdoor media (billboards).